Hubungan pola asuh orang tua dengan sikap remaja putri tentang kesehatan reproduksi di SMA Negeri 18 Medan tahun 2011 - Emilda AS; Meliani Sukmadewi HRP (Jurnal Kesehatan Ibu dan Anak, 2013)
Teenage daughter vulnerable to maternal mortality, infant and child mortality, unsafe abortion, STl, drug and violence/sexual abuse. Older people as a social environment arc expected to apply first teen parenting that emphasizes the availability of an open dialogue between teens and parents about adolescent reproductive health to have the right attitude about reproductive health. This study aims to determine the relationship parenting parents with teenage daughters’ attitude about reproductive health in SMA Negeri 18 Medan 2011. Design used in this study is descriptive correlation. Sample in the study was a teen daughter SMA Negeri 18 fields totaling 170 people. The sample using systematic random sampling. The research results from 170 respondents, the majority 74.1% were category authoritative parenting (democratic) and the majority 71.2% positive. Result of statistical test with chi-square about reproductive health. Expected to be input to the educational institution to collaborate with public health officials in the Directorate of Youth and Reproductive Rights Protection, BKKBN to activate PIK-KRR in educational institutions and parents should be able to apply the pattern that emphasizes the availability of foster open dialogue about reproductive health in adolescents .